Computational Design and Evaluation of Formaldehyde-Free Modified Tannins for Enhanced Copper Ion Removal - November Rianto Aminu; Suryadi Joyopranoto; Tiffany Octavia Kusumawijaya; Margareta Novian Cahyanti; Parsaoran Siahaan (Jurnal Kimia Sains dan Aplikasi, 2025)
Pollution from heavy metal ions, such as copper (Cu2+), in textile wastewater poses a significant environmental challenge. Modified condensed tannins (TyD) show promise as coagulants for heavy metal removal, but current formaldehyde-based modification methods are concerning due to formaldehyde’s carcinogenic nature. This in silico study aimed to optimize TyD design by replacing formaldehyde with safer alternatives: acetone (TyDA), ethyl methyl ketone (TyDE), and benzaldehyde (TyDB), and evaluating their interaction stability with Cu2+ ions. Using Density Functional Theory (DFT) with a B3LYP-D3/6-31G(d,p) basis set, this study performed calculations for interaction energy (Ei) and complex activity (HOMO-LUMO, affinity, electronegativity, energy gap). The results indicated that the TyDB-1 design exhibited the most optimal interaction energy with Cu2+ ions, showing an Ei value of −943.39 kJ.mol−1 for TyD…Cu2+ and −1,271.86 kJ.mol−1 for TyD…Cu2+…TyD interactions. In the single TyD…The Cu2+ complex, TyDB-1, demonstrated superior stability, stronger binding, and better Cu2+ attraction compared to the formaldehyde-modified TyDF, despite a higher energy gap (1.354 eV vs. 1.090 eV). A higher HOMO-LUMO energy gap indicates reduced electronic reactivity and enhanced complex stability, signifying that TyDB-1 forms a more stable coordination with Cu2+ ions. However, in the presence of an additional TyD molecule (TyD…Cu2+…TyD), TyDB-1, while showing strong bonds and good attraction, was found to be more reactive than TyDF. Overall, TyDB-1 represents a promising, safer alternative for Cu2+ coagulation, highlighting the utility of computational chemistry in designing high-performance coagulants.